Hydrogen (H2) Inhibits Isoproterenol-Induced Cardiac Hypertrophy via Antioxidative Pathways - Zhang, Yaxing; Xu, Jingting; Long, Zhiyuan; Wang, Chen; Wang, Ling; Sun, Peng; Li, Ping; Wang, Tinghuai (Frontiers in Pharmacology, 2016)
Background & Purpose: Hydrogen (H2) has been shown to have a strong antioxidant effect on preventing oxidative stress-related diseases. The goal of the present study is to determine the pharmacodynamics of H2 in a model of isoproterenol (ISO)-induced cardiac hypertrophy. Methods: Mice (C57BL/6J; 8-10 weeks of age) were randomly assigned to four groups: Control group (n=10), ISO group (n=12), ISO plus H2 group (n=12), H2 group (n=12). Mice received H2 (1ml/100g/day, intraperitoneal injection) for 7 days before ISO (0.5mg/100g/day, subcutaneous injection) infusion, and then administered ISO with or without H2 for another 7 days. Then, cardiac function was evaluated by echocardiography. Cardiac hypertrophy was reflected by heart weight/body weight, gross hearts and heart sections stained with H&E, and relative ANP and BNP mRNA levels. Cardiac reactive oxygen species (ROS), 3-nitrotyrosine and p67 (phox) levels were analyzed by Dihydroethidium staining, immunohistochemistry and western blotting, respectively. For in vitro study, H9c2 cardiomyocytes were pretreated with hydrogen rich medium for 30 minutes, and then administrated with ISO (10 μM) for the indicated time. The medium and ISO were re-changed every 24 hours. Cardiomyocyte surface areas, relative ANP and BNP mRNA levels, the expression of 3-nitrotyrosine, and the dissipation of mitochondrial membrane potential (MMP) were examined. Moreover, the expression of ERK1/2, p-ERK1/2, p38, p-p38, JNK, p-JNK were measured by western blotting both in vivo and in vitro. Results: Intraperitoneal injection of hydrogen prevents cardiac hypertrophy and improves cardiac function in ISO-infused mice. Hydrogen rich medium blocks ISO-mediated cardiomyocytes hypertrophy in vitro. Hydrogen blocked the excessive expression of NADPH oxidase and the accumulation of ROS, attenuated the decrease of MMP, and inhibited ROS-sensitive ERK1/2, p38, JNK1/2 signaling pathways. Conclusions: H2 inhibited ISO-induced cardiac/cardiomyocytes hypertrophy both in vivo and in vitro, and improved the impaired left ventricular function. H2 exerts its protective effects partially through blocking ROS-sensitive ERK1/2, p38, JNK1/2 signaling pathways.